2020
DOI: 10.48550/arxiv.2009.10379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forwarding techniques for the global stabilization of dissipative infinite-dimensional systems coupled with an ODE

Swann Marx,
Lucas Brivadis,
Daniele Astolfi

Abstract: This paper deals with the stabilization of a coupled system composed by an infinite-dimensional system and an ODE. Moreover, the control, which appears in the dynamics of the ODE, is subject to a general class of nonlinearities. Such a situation may arise, for instance, when the actuator admits a dynamics. The openloop ODE is exponentially stable and the open-loop infinite-dimensional system is dissipative, i.e., the energy is nonincreasing, but its equilibrium point is not necessarily attractive. The feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Indeed, such a methodology has been proved to be efficient for nonlinear systems. Among these techniques, we aim at using the forwarding method that has been first designed for finite-dimensional systems in cascade form [35,2] and then extended for some hyperbolic systems [47] in the regulation context, and for abstract systems [29] in the stabilization context. In [47], it is shown that a strict Lyapunov functional 1 is needed for open-loop stable systems that we aim at regulating.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such a methodology has been proved to be efficient for nonlinear systems. Among these techniques, we aim at using the forwarding method that has been first designed for finite-dimensional systems in cascade form [35,2] and then extended for some hyperbolic systems [47] in the regulation context, and for abstract systems [29] in the stabilization context. In [47], it is shown that a strict Lyapunov functional 1 is needed for open-loop stable systems that we aim at regulating.…”
mentioning
confidence: 99%
“…We aim at showing that such a problem can be solved by means of an integral action and an output feedback control law. The proposed design is based on the forwarding method (see e.g., [47] or [29]). Note that in Section 5.1, we focus on the linearized version of the system.…”
mentioning
confidence: 99%